METHOD OF DATA EXPRESSION FROM THE UKRAINIAN CONTENT BASED ON THE ONTOLOGICAL APPROACH - Lytvyn, V. V.; Vysotska, V. A.; Hrendus, M. H. (Radio Electronics, Computer Science, Control, 2018)
Context. Nowadays there is a constantly increasing interest to the application of the intelligent systems (IS) in different areas such as information technologies (IT), engineering, medicine, biology, ecology, geography, jurisprudence etc. At the heart of architecture of modern IS’s knowledge bases (KB) are used, which are formed due to the subject area (SA), where the given IS is used. The main part of KB is ontology as clearly structured SA’s model, systematic set of terms, which explain the connections between objects of this SA. Ontologies are generally accepted and widely used in different branches of science such as knowledge engineering, presentation of knowledge, information search, knowledge management, database design, information modeling and object-oriented analysis. In particular, Gather company in their researches of IT-market attributed the use of taxonomy/ontology in his area. Consequently, research of syntactic ontological structures of KB, construction and research of optimal algorithm for syntactic analysis of Ukrainian language texts and the development of software-algorithmic means of content, automatic referencing of texts, gathering knowledge, translation etc. are relevant. Objective. The goal of the work develop a software system for formalizing the rules of syntax of the Ukrainian language in the form of an ontological basis of knowledge for the purpose of its use for working out natural language texts in the Ukrainian language. Method. Methods of solving the problem of creating a consolidated resource based on ontological KB were chosen decision trees, IDEF5 methodology and ontology construction methodology. The results of syntactic analysis work are taken into account by associative-semantic context analysis to optimize the process of constructing associative context relationships between words and sentence combinations within the hierarchical network of ontological BB. Results. A consolidated information resource is created – an ontological KB of parsing analysis of Ukrainian-language text documents with the help of Protégé 3.4.7. Conclusions. The method of data extraction based on ontological BZ and FPGA language is developed for the further development of a consolidated information resource for the syntactic elaboration of text documents. As a result, an ontological type of KB with FPSM was created. The syntactic structure of the input sentence is the foundation and frame for the next, not less important step – semantic analysis. This ontological KB of the consolidated LR of syntactic elaboration of Ukrainian-language text documents serves as a powerful basis for further development of an automated IS for parsing Ukrainian-language texts